Pengaruh Pendidikan dan Beban Kerja terhadap Kompensasi serta Dampaknya terhadap Kinerja Tenaga Fasilitator Lapangan pada Satuan Kerja Penyediaan Perumahan Provinsi Jambi - Sunarti, Sunarti; Yamali, Fakhrul Rozi; Sudirman, Sudirman (Universitas Batanghari, 2024)
The purpose of this study is to describe the TFL performance, workload, compensation, and education in the Jambi Province Housing Provision Working Unit. It also seeks to ascertain and evaluate the impact of workload, compensation, and education on TFL performance in the Jambi Province Housing Provision Working Unit. Both quantitative and descriptive approaches of verification were employed in this study. A saturation or census sampling technique was used to determine the study's sample. The study's sample is the full TFL population in 2022, which is limited to 63 people. The path analysis method is used in this study. Employee education at the Jambi Province Housing Provision Work Unit is described as belonging to the